LA PERCEPTION DES INFIRMIèRES ET DES INFIRMIERS EN SOINS PéRIOPéRATOIRES EN CE QUI CONCERNE LES COMPéTENCES : RéPERCUSSIONS SUR L’IMMIGRATION - Gillespie, Brigid; Chaboyer, Wendy; Lingard, Shirley; Ball, Sharon (Operating Room Nurses Association of Canada Journal, 2012)
Background. Nurses’ recognition of their own level of skills and abilities (ie perceived competence) is a prerequisite for ensuring they can practice in a safe manner. The demand for competence, in the operating room, may vary between clinical environments. It is, however, unclear what competency levels migrating nurses need in order to be deemed safe. Aim. This paper describes Canadian and Australian nurses’ levels of perceived perioperative competence and discusses these results in the context of nurse migration. Method. A survey was distributed to operating room nurses in six hospital sites (three in Canada and three in Australia). Perioperative competence was measured with a 40-item self-report survey which consisted of six domain subscales: foundational knowledge and skills; leadership; collaboration; proficiency; empathy; and professional development. Non-parametric tests were used to describe differences between groups based on country of origin, years of experience, and specialty qualifications. Results. Canadian and Australian nurses reported their overall competency levels as high across all domains. Significant differences were found, between countries, in three of the six competency domains; foundational knowledge and skills (p<.001), collegiality (p=.023), and empathy (p<.0001). Conclusions. Describing perioperative competence cross-nationally represents the first step in generating international dialogue around educational preparation for migrating nurses. The increasing global mobility of nurses makes it imperative to further standardise, with an international perspective, knowledge and practice expectations in perioperative settings.